Ancaman Keanggotaan Koperasi Persusuan Akibat Kehadiran Kolektor Susu - Salsabilah, Khansa Nurul; Sulistyanti, Marina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research was carried out in October 2023 using a literature study research method related to problems with dairy cooperative membership due to the presence of milk collectors. This article discusses several examples of cases related to institutional problems in dairy cooperatives caused by milk collectors with the aim of finding out how the presence of milk collectors can be a threat to dairy cooperative membership. Based on case studies from two studies related to the presence of milk collectors in cooperative membership, it can provide an illustration of how building member trust is very important in maintaining cooperative membership. Even though the service and price of milk provided between collectors and cooperatives is not much different, the trust of members greatly influences the institutional membership of cooperatives. Institutional dynamics or problems in external cooperatives can disrupt the stability of the cooperative and members' trust, thereby opening up gaps for external parties who can make members switch. Approach efforts from cooperatives to members are needed to restore members' trust, such as establishing good relationships and communication as well as regular evaluations by carrying out controls and visits